1998
DOI: 10.1177/106591299805100311
|View full text |Cite
|
Sign up to set email alerts
|

International Crises and Linkage Politics: The Experiences of the United States, 1953-1994

Abstract: This study assesses the effects of U.S. involvement in international cri ses on the domestic popularity of American presidents for all major classes of voters. Using a time series analysis of monthly presidential approval and crisis involvement between 1953 and 1994, and controlling for eco nomic conditions and structural features of presidential popularity, it is apparent that crisis activity does increase the president's popularity, albeit by a very small margin. This result holds for both overall approval l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…Some scholars find a correlation between war and the increased leverage it gives the president (Norrander and Wilcox ; Parker ; Rudalevige ). James and Rioux (), on the other hand, find war has the opposite effect and actually affects the president negatively. Howell () and Marra, Ostrom, and Simon ) find war matters, though the relationship is not consistent for all conditions.…”
Section: Dependent and Independent Variablesmentioning
confidence: 99%
“…Some scholars find a correlation between war and the increased leverage it gives the president (Norrander and Wilcox ; Parker ; Rudalevige ). James and Rioux (), on the other hand, find war has the opposite effect and actually affects the president negatively. Howell () and Marra, Ostrom, and Simon ) find war matters, though the relationship is not consistent for all conditions.…”
Section: Dependent and Independent Variablesmentioning
confidence: 99%
“…Richards et al (1993) posit that the primary domestic utility of force usage derives not from its capacity to temporarily divert popular attention from leadership failings, but from the opportunity it affords leaders to offset domestic perceptions of managerial incompetence through international victories (see also Downs and Rocke's [1995] work on "gambling for resurrection"). James and Rioux, 1998;Bennett and Nordstrom, 2000). Employing psychological factors that take intent into explicit account, Keller and Foster's (2009) discovery of the positive effects of leaders' self-confidence and of their own beliefs about their ability to control external events on force 15 For instance, the failure to resolve this issue leaves confusion regarding which states distressed leaders target during periods of domestic difficulty.…”
Section: Resultsmentioning
confidence: 99%
“…He demonstrates support for his argument using US presidential approval data. Several other studies have found that the average rally effect, though positive, is quite modest (Lian and Oneal 1993; Oneal and Bryan 1995; James and Rioux 1998).…”
Section: Responding To Economic Turmoilmentioning
confidence: 85%